The Role of Faith and Faith Schooling in Educational, Economic, and Faith Outcomes - Andrew McKendrick; Ian Walker (Institute of Labor Economics (IZA), 2020)
We examine the roles played by intrinsic religiosity and faith-based education in both short and long-term outcomes among young people in England. England is a good laboratory for this work as it has a substantial share of publicly funded faith schools. This is in contrast to the US, where much of the literature of faith (mostly Catholic) schools is rooted, and other developed countries who tend to have faith schools that are fee-paying. We use a cohort study from England that contains a detailed and extensive range of individual, parental, household, and secondary school level controls. In the absence of any convincing quasi-experimental method to identify the effects of interest, the research relies on the very detailed nature of the data to support a methodology based on Ordinary Least Squares (OLS), augmented by the Oster (2017) test, to provide plausible and robust estimates of the impacts of both religious belief and faith schooling. We show that an individual's intrinsic religiosity is an important driver of short-term educational outcomes (such as age 16 test scores) and some longer-term outcomes (Christian belief at age 25), while faith-based schooling plays a lesser role. Faith schools perform well in terms of their ethos and environment, with lower incidences of bullying within them and greater parental satisfaction with how they operate.
Keywords: I21; Z12; 330; religiosity; faith schools; belief